Desining a new fractal absorbent chip consisting of metamaterials to decrease the impact of electromagnetic waves on human beings - نعمان, زينب; السموءل صالح (Latakia University Journal -Engineering Sciences Series, 2023)
In the last few years, the scientific researches have focused on developing the structure of used materials and the way with which they deal with the electromagnetic radiations to give particular specifications according to its practical use. Researchers have gotten Metamaterials and found out that they have new features which are not existed in nature, and when they interact with electromagnetic waves, they give a negative electrical permittivity and magnetic permeability. Thanks to these peculiar features of metamaterials, its design and usage have become a common subject in many domains, and the most important of which is the domain of microwave and optical communications. Also, the intrest in using fractal geometry has increased due to its key role in getting multi bands, wide bandwidth, the possibility of controlling the resonance frequency, and giving more parameters in the design. In this paper, a chip design, that acts as an absorber composed of dual band metamaterials based on Minkowski geometry, has been proposed. High absorption rates have been reached ( 99%) in GSM frequency bands, by using Computer Stimulation Program CST.